Excitation functions of proton induced nuclear reactions on W-nat up to 40 MeV - Khandaker, Mayeen Uddin; Uddin, M.S.; Kim, K.; Lee, M.W.; Kim, K.S.; Lee, Y.S.; Kim, G.N.; Cho, Y.S.; Lee, Y.O. (Elsevier, 2008)
We measured the excitation functions for the production of the (181,) Re-182m,Re- 182g,Re- 183 184g,Re- 186 radioisotopes from proton bombardment of natural tungsten by using a stacked-foil activation technique in the energy range from threshold energy to 40 MeV at the MC50 cyclotron of the Korea Institute of Radiological and Medical Science. The results were compared with the earlier reported experimental data and the model calculations using codes TALYS and ALICE-IPPE. The present values are in good agreement with some of the previously reported literature. The integral yields for thick targets were also deduced from the measured excitation functions of the produced radioisotopes. The deduced yield values were compared with the available directly measured thick target yield, and found acceptable agreement. The investigated radioisotope Re-186 has remarkable applications in the field of nuclear medicine, whereas the data of Re-183,Re- 184g have potential applications in thin layer activation analysis. (c) 2008 Elsevier B.V. All rights reserved.